SCALE WARS: AN EXPLORATION OF ‘INTERVAL-VALUED SCALE’ ATTRIBUTES IN MARKETING RESEARCH - Pagiaslis, Anastasios; Themistocleous, Christos; Smith, Andrew; Wagner, Christian (My University, 2017)
Crisp single-point capturing scales such as Semantic Differential, Likert and Stapel are commonly used in marketing research. Even though crisp single-point capturing scales offer valuable information regarding the respondents’ perceptions on a specific topic, more recently-developed scales allow responses to be recorded by specifying an interval from the provided scale. Wagner et al., (2015) introduce interval-valued scales in surveys not only providing respondents with the ability of recording their answer accurately but also allowing the representation of uncertainty that may be included in respondents’ answers. Miller et al., (2014) note that interval-valued survey data, modelled through the Interval Agreement Approach (IAA), offer richer information compared to traditional single-point capturing scales. The aim of this paper is to explore Interval-Valued Scales (IVS) in a marketing research context and provide comparative results of an initial study between IVS and Semantic Differential Scales (SDS). This initial comparative exploration of IVS vs SDS is based on scale attributes as advocated by Preston & Colman (2000) namely: i) Ease of use, ii) Speed of use, iii) Ability to precisely record desired answers, iv) Adequate expression of exact thoughts and feelings, v) Certainty/Uncertainty with personal answers and vi) Overall satisfaction with each scale.
Keywords: Marketing Management; Methodological; Measurement scales; Survey design; Management